Elution of Hg-containing substances from CeO2-MnO2/TiO2 adsorbent in H2S atmosphere by CuCl2 solution. (1st January 2023) - Liu, Zhuang; Zhou, Jinsong; Zhou, Qixin; Zhou, Lingtao; Lu, Yang; Li, Bohao; Wang, Tang
Highlights: The proportion and elution difficulty of Hg-containing substances followed HgS(black) > HgS(red) > HgO(red). The elution was basically completed within 2 min with efficiency of 98.38 %. Higher concentration, higher temperature and lower pH were conducive to the elution. The elution followed the first-order two-domain model in which HgO and HgS belonged to the rapid and slow part. Abstract: Mercury (Hg) pollution in syngas has received increasing attention. The adsorbent can effectively remove Hg from syngas, and the removal of Hg-containing substances before the landfill of spent adsorbent can avoid Hg secondary pollution effectively. H2 S was the main resource for the generation of stable and insoluble HgS in syngas. In this work, the elution of Hg-containing substances from the spent CeO2 -MnO2 /TiO2 (Ce-Mn/Ti) adsorbent in H2 S atmosphere by CuCl2 solution was studied. The optimum temperature for Ce-Mn/Ti to remove Hg 0 in H2 S atmosphere was 160 °C. The Hg-containing substances were HgS (black), HgS (red), and HgO (yellow), in which both the proportion and elution difficulty followed the descending order of HgS(black) > HgS(red) > HgO(yellow). The elution was basically completed within 2 min with excellent efficiency of 98.38 %. Higher concentration, higher temperature, and lower pH were conducive to the elution, and the optimum concentration and temperature were 1.0 mol/L and 45 °C respectively. The elution followed the first-order two-domain model, in which HgO and HgS were the rapid and slow part respectively. The elution not only retained the favorable mesoporous structure, but also enabled the eluted Ce-Mn/Ti adsorbent to have a higher efficiency and a better stability on Hg removal by loading the active component of CuCl2 . This study demonstrated that CuCl2 could be a good eluent for the elution of Hg-containing species and the reutilization of metal oxide-based adsorbent.